2014
DOI: 10.1093/mnras/stu1753
|View full text |Cite
|
Sign up to set email alerts
|

The thickness of a weakly magnetized accretion flow inside the last stable orbit of a Kerr black hole

Abstract: If accretion disc contains weak frozen-in entangled magnetic fields, their dynamical effect may be important inside the last stable orbit because of the decompression near the sonic point. Here, I consider the radial and vertical structure of a nearly free-falling flow inside the last stable orbit of a thin disc around a Kerr black hole. The thickness of such a flow is determined primarily by the vertical stress created by radial and azimuthal magnetic fields. The thickness is predicted to oscillate vertically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Matter enters ballistic plunge orbits at that radius with very little dissipation or further emission as it falls into the black hole. Later work in which the effect of magnetic fields are considered has suggested that stresses can and do occur at the ISCO leading to dissipation and excess emission as matter enters the plunge region (Reynolds & Armitage 2001, Hawley & Krolik 2002, Machida & Matsumoto 2003, Shafee et al 2008, Zhu et al 2012, and Abolmasov 2014. One of the most detailed studies, by Zhu et al (2012) shows that further inward flow can cause a weak power-law-like continuum composed of ever hotter black body (bb) emission as matter falls further.…”
Section: The Plunge Regionmentioning
confidence: 99%
“…Matter enters ballistic plunge orbits at that radius with very little dissipation or further emission as it falls into the black hole. Later work in which the effect of magnetic fields are considered has suggested that stresses can and do occur at the ISCO leading to dissipation and excess emission as matter enters the plunge region (Reynolds & Armitage 2001, Hawley & Krolik 2002, Machida & Matsumoto 2003, Shafee et al 2008, Zhu et al 2012, and Abolmasov 2014. One of the most detailed studies, by Zhu et al (2012) shows that further inward flow can cause a weak power-law-like continuum composed of ever hotter black body (bb) emission as matter falls further.…”
Section: The Plunge Regionmentioning
confidence: 99%
“…We have considered the results of a thick disc MHD simulation from Abolmasov (2014), namely the run B1h presented in this work. Simulation was performed using the numerical code HARM2D that solves ideal MHD equations in Kerr metric (Gammie et al 2003;Noble et al 2006).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Numerical simulations of thick MHD discs support the assumption of Keplerian rotation in the inner parts of thick accretion discs and even inside the last stable orbit (Penna et al 2010). We have considered the results of a thick disc MHD simulation from Abolmasov (2014), namely the run B1h presented in this work. Simulation was performed using the numerical code HARM2D that solves ideal MHD equations in Kerr metric (Gammie et al 2003;Noble et al 2006).…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation